Synchronous Voice Applied Customer Access based on IEEE 802.11 - Kajackas, A.; Pavilanskas, L.; Vindašius, A. (Elektronika ir Elektrotechnika, 2007)
The analysis of infrastructure IEEE 802.11 protocol based wireless access network with point coordination (PCF) for synchronized voice and reliable quality data transmission is presented. It is shown, that it is possible to create wireless customer access with wired network quality by synchronizing voice source coders with beacon periods. The analysis of this system has been validated by simulations in Opnet. The modeling additionally evaluates wireless channel capacity in terms of provided voice channels while keeping reasonable packet loss. The defined capacity is greater than capacity evaluations presented in other publications. Ill. 7, bibl. 11 (in English; summaries in English, Russian and Lithuanian).